Inhibitory effect of (2S)-pinocembrin from goniothalamus macrophyllus on the prostaglandin E2 production in macrophage cell lines - Hilwan Yuda, Teruna; Kamal, Rullah; Hendra, Rudi; Utami, Rahayu; Islami, Deri; Siti Munirah, Mohd Faudzi; Mohd Fadhlizil Fasihi, Mohd Aluwi; Lam, Kok Wai (John Wiley & Sons Ltd, 2024)
Pinocembrin (PCB), a flavonoid known for its anti-inflammatory properties, has been approved for various clinical trial applications. To evaluate deeper into the anti-inflammatory potential of the specific enantiomer of natural PCB, we conducted the first investigation into the efficacy of the pure enantiomer (2S)-PCB in modulating inflammatory mediators induced by lipopolysaccharide (LPS) in both murine RAW 264.7 and human U937 macrophage cell lines. This particular compound was isolated from Goniothalamus macrophyllus (Annonaceae), a native plant of Indonesia. This plant has been used traditionally as an herbal medicine to alleviate inflammation. (2S)-PCB was isolated from the stem bark of G. macrophyllus by defatting with n-hexane followed by maceration with methanol. Purification was performed using several chromatographic techniques. The absolute configuration was determined using electronic circular dichroism (ECD) spectroscopy. This compound was then tested for its inhibitory activity on prostaglandin E2 (PGE2) and subjected to docking simulations. The results indicated that (2S)-PCB significantly suppressed the production of PGE2 induced by LPS in both RAW 264.7 and U937 cell lines. The docking simulations revealed that (2S)-PCB reduced PGE2 levels by suppressing mitogen-activated protein kinase (MAPK) activation through inhibiting p38 and extracellular signal-regulated kinases (ERK). These findings suggest that the compound may prevent worsening of septic shock caused by bacterial infection.